Pengembangan E-LKPD Berbasis Problem Based Learning (PBL) Terintegrasi Al-Quran dan Hadis Pada Materi Keanekaragaman Tumbuhan - Putri, Adinda Opmila; Ulfa, Syarifah Widya (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to develop a digital student worksheet (E-LKPD) utilizing Liveworksheet, based on Problem-Based Learning (PBL) and integrated with values from the Qur'an and Hadith, focused on the topic of Plant Diversity. The research employed a Research and Development (R&D) approach using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Research instruments included expert validation questionnaires for content and media, teacher and student response questionnaires to assess practicality, as well as pre-test and post-test instruments to evaluate effectiveness. The trial subjects were students from classes X MIPA-1 and X MIPA-2 at SMA MAL Medan, involving 60 students and one biology teacher. Validation results showed that the developed E-LKPD was rated as highly relevant by content experts (93.75%) and media experts (97.41%). Practicality assessment yielded scores of 85.7% by the biology teacher and 93.5% by the students, both categorized as very practical. Effectiveness testing showed a learning outcome improvement of 87.4%, indicating a high level of effectiveness. Thus, the PBL-based E-LKPD integrated with Qur'anic and Hadith values on the topic of Plant Diversity is valid, practical, and effective, making it suitable for implementation in high school biology instruction.